PENGARUH VARIASI LAMA WAKTU PEREBUSAN BUNGA TELANG (Clitoria ternatea L.) TERHADAP KANDUNGAN ALKALOID DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Muhamad Yoga Firmansyah; Alip Desi Suyono Saputri; Rizka Wahyu Syahputra; Pra Panca Bayu Chandra (Jurnal Farmasi IKIFA, 2026)
Butterfly pea flower (Clitoria ternatea L.) contains various secondary metabolites, including alkaloids. Boiling is commonly used by the community to prepare butterfly pea flower, but boiling duration may affect the level of active compounds extracted. This study aimed to determine the effect of boiling time variation on the alkaloid content of butterfly pea flower decoction and to identify the optimal boiling time. An experimental method was conducted using boiling times of 10, 20, and 30 minutes. Qualitative alkaloid identification was performed using Mayer, Wagner, and Dragendorff reagents, while total alkaloid content was determined by UV-Vis spectrophotometry using bromocresol green (BCG) as a complex-forming reagent. The results showed that all samples tested positive for alkaloids. The average alkaloid contents at boiling times of 10, 20, and 30 minutes were 0.1548, 0.2046, and 0.2917 mg CE/mL, respectively. Statistical analysis indicated a significant difference among treatments (p<0.05). The 30-minute boiling treatment produced the highest alkaloid content and was considered the optimum boiling time.